2020
DOI: 10.1029/2020jc016372
|View full text |Cite
|
Sign up to set email alerts
|

Transient Enhancement and Decoupling of Carbon and Opal Export in Cyclonic Eddies

Abstract: Given their ephemeral nature, eddies have proven difficult to study, with contrary results from field observations that typically sample at the center during a specific stage of an eddy lifespan. Using the natural occurring radionuclide 234Th, we examined particle fluxes within two cyclonic eddies (CEs) at different evolutionary stages (mature stage eddy, C2, and a decay stage eddy, C1) in the oligotrophic western South China Sea (SCS). Using a 1‐D steady state model, 234Th derived particulate organic carbon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…Cyclonic eddy‐mediated biogenic Si, particulate C, and N fluxes across the EC and EE during non‐bloom periods were significantly higher than the non‐eddy reference periods (2 months before or after eddy passage, the monthly average or the long‐term annual average). These results agree with the more focused studies of individual wind‐generated mesoscale eddies that form in the lee of the Hawaiian Islands (e.g., Benitez‐Nelson et al 2007; Maiti et al 2008) and cyclonic eddies in the Western South China Sea (Zhou et al 2020), but differ from studies that found little to no enhancement of particulate C and biogenic Si export in the cyclonic eddies of the South China Sea basin (e.g., Yang et al 2015), or seasonally variable particulate C enhancement in the Canary Current region of the North Atlantic Ocean (Alonso‐González et al 2013). We argue that the underlying differences among all of these studies are linked to the evolutionary stage of a single cyclonic eddy and the low spatial resolution of sampling, which often focused on the EC alone.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Cyclonic eddy‐mediated biogenic Si, particulate C, and N fluxes across the EC and EE during non‐bloom periods were significantly higher than the non‐eddy reference periods (2 months before or after eddy passage, the monthly average or the long‐term annual average). These results agree with the more focused studies of individual wind‐generated mesoscale eddies that form in the lee of the Hawaiian Islands (e.g., Benitez‐Nelson et al 2007; Maiti et al 2008) and cyclonic eddies in the Western South China Sea (Zhou et al 2020), but differ from studies that found little to no enhancement of particulate C and biogenic Si export in the cyclonic eddies of the South China Sea basin (e.g., Yang et al 2015), or seasonally variable particulate C enhancement in the Canary Current region of the North Atlantic Ocean (Alonso‐González et al 2013). We argue that the underlying differences among all of these studies are linked to the evolutionary stage of a single cyclonic eddy and the low spatial resolution of sampling, which often focused on the EC alone.…”
Section: Discussionsupporting
confidence: 89%
“…Mesoscale cyclonic eddies enhance biological production, influence food web structure, and hence particle formation and export by facilitating the injection of nutrient rich deep water into well‐lit surface waters (McGillicuddy 2016; Resplandy et al 2019; Zhou et al 2020). Understanding the magnitude of cyclonic eddy effects on ocean biogeochemistry is confounded by the inherent spatio‐temporal variability of the open ocean and the difficulty in not only identifying mesoscale cyclonic eddy features, but also comparing eddy‐mediated changes to other, presumably uninfluenced ocean waters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations